2021
DOI: 10.1111/mve.12509
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐CT imaging of Onchocerca infection of Simulium damnosum s.l. blackflies and comparison of the peritrophic membrane thickness of forest and savannah flies

Abstract: Onchocerciasis is a neglected tropical disease (NTD) caused by Onchocerca Diesing 1841 (Spirurida: Onchocercidae) nematodes transmitted by blackflies. It is associated with poverty and imposes a significant health, welfare and economic burden on many tropical countries. Current methods to visualize infections within the vectors rely on invasive methods. However, using micro‐computed tomography techniques, without interference from physical tissue manipulation, we visualized in three dimensions for the first ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In addition, iodine staining sometimes results in blurry edges of some key tissues and structures [19]. To increase X-ray absorption of lowdensity tissues and enhance overall contrast, subsequent sand flies were stained for one week by immersion in a solution of 1% phosphotungstic acid (PTA) in 80% ethanol, with continual swirling on a laboratory mixer and a change to fresh staining solution mid-period [16]. Unlike the iodine stain, PTA staining penetrates more slowly into the tissues, but it binds permanently and results in sharp tissue differentiation [18,19], so material could be held for a lengthy period before scanning without loss of stain.…”
Section: Stainingmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, iodine staining sometimes results in blurry edges of some key tissues and structures [19]. To increase X-ray absorption of lowdensity tissues and enhance overall contrast, subsequent sand flies were stained for one week by immersion in a solution of 1% phosphotungstic acid (PTA) in 80% ethanol, with continual swirling on a laboratory mixer and a change to fresh staining solution mid-period [16]. Unlike the iodine stain, PTA staining penetrates more slowly into the tissues, but it binds permanently and results in sharp tissue differentiation [18,19], so material could be held for a lengthy period before scanning without loss of stain.…”
Section: Stainingmentioning
confidence: 99%
“…Many of those studies have been of larger Diptera: to achieve sufficient resolution in the scanning of small Diptera is more challenging due to staining issues and the increased scan times needed. However, a recent study of the infection of Simulium blackflies with Onchocerca nematodes demonstrated the feasibility of using micro-CT to scan small flies, revealing a parasite in the flight muscles of the fly [16].…”
Section: Introductionmentioning
confidence: 99%
“…With this technique internal morphological alterations can be visualized at very high-resolution 14 – 17 and by time resolved X-ray imaging also dynamic processes, such as movement of air trapped in an “air bubble” from inside the pupae to the space between the adult insect and the puparium 18 . Modern micro-CT systems can yield virtual sections of the insect brain and the optical lobe 19 , 20 and even visualise infectious nematodes in its vector, black flies 21 .…”
Section: Introductionmentioning
confidence: 99%